An ethnographic appreciation of sexual vilification of women in print media: case of H-Metro - Chipungudzanye, Tatenda (Midlands State University, 2018)
This study is based on sexual vilification of women in H-Metro with the research located in the connections of the theory of sexual objectification, picture theory and tabloid theory. The study is guided by the works of Fredrickson and Roberts, and Harmsworth. The study is of qualitative nature drawing extensive material derived from the archives where fifty (50) newspaper articles were studied, ten (10) interviews conducted as well as my own perceptions as a participant observer. I fixed my epistemological and methodological gaze on sexual vilification of women from January 2015 to August 2017 where I conducted my case study as a participant observer at H-Metro. Women‟s sexual vilification experiences create discursive lenses for re-imagining representations in the press. The major finding of this study is that women are sexually vilified by being given derogatory names. Women are portrayed as hookers, prostitutes, ladies of the night, thigh vendors and side chicks. The study thematically presented the data while hermeneutics, textual analysis and discourse analysis were used to examine the data. My conclusion, in part, shows that patriarchy as well as political economy of the media have influenced sexual vilification discourses against women in H-Metro.